2007
DOI: 10.1021/jp065917k
|View full text |Cite
|
Sign up to set email alerts
|

Simple Physics-Based Analytical Formulas for the Potentials of Mean Force for the Interaction of Amino Acid Side Chains in Water. 2. Tests with Simple Spherical Systems

Abstract: Simple analytical functions consisting of electrostatic, polarization, Lennard-Jones or modified Lennard-Jones, and cavity terms are proposed to express the potentials of mean force analytically for spherical particles interacting in water. The cavity term was expressed either through the molecular-surface area of the solute or by using the Gaussian-overlap model of hydrophobic hydration developed in paper 1 of this series. The analytical expressions were fitted to the potentials of mean force of a methane hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(81 citation statements)
references
References 50 publications
(88 reference statements)
2
76
1
2
Order By: Relevance
“…The model reproduces the desolvation maxima. 14,15 The Gaussian overlap model of the solvent and counter-ion density in the first solvation sphere is supported by the spatial distribution of water molecules and counter-ions obtained from simulation of model systems, where counter-ions and water density around a solute have clear maxima in the center of the first solvation sphere (Figures 9 and 10 in ref 38). …”
Section: Theorymentioning
confidence: 88%
“…The model reproduces the desolvation maxima. 14,15 The Gaussian overlap model of the solvent and counter-ion density in the first solvation sphere is supported by the spatial distribution of water molecules and counter-ions obtained from simulation of model systems, where counter-ions and water density around a solute have clear maxima in the center of the first solvation sphere (Figures 9 and 10 in ref 38). …”
Section: Theorymentioning
confidence: 88%
“…In one of these papers,2 we showed that the derived expression for the cavity creation term reproduces the features of the cavity part of the potentials of mean forces of homo- and heterodimers of simple spherical solutes in water very well. In the third paper3 of the series, we considered models of pairs of identical nonpolar amino acid side-chain models.…”
Section: Introductionmentioning
confidence: 86%
“…In this work, the parameters mentioned above were determined by least-squares fitting of the analytical expression for the free energy of two side chains interacting in water (eqs 1–4) to the PMFs determined from MD simulations, as in our earlier work. 3,4,6,7 …”
Section: Theorymentioning
confidence: 99%
“…The expression for Δ F cav of spheroidal particles was derived in ref 3 on the basis of the Gaussian-overlap model of hydrophobic association introduced in that work and is given by eq 14. This term accounts for the free-energy contribution due to restructuring water molecules around a hydrophobic dimer and has been derived and discussed in detail in ref 2.…”
Section: Theorymentioning
confidence: 99%